2021
DOI: 10.1186/s12872-021-01982-y
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid regurgitation in ischemic mitral regurgitation patients: prevalence, predictors for outcome and long-term follow-up

Abstract: Background Functional tricuspid regurgitation (FTR) is common in left-sided heart pathology involving the mitral valve. The incidence, clinical impact, risk factors, and natural history of FTR in the setting of ischemic mitral regurgitation (IMR) are less known. Method We conducted a cohort study based on data collected from January 2012 to December 2014. Patients diagnosed with IMR were eligible for the study. The median follow-up was 5 years. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Previous studies have reported an association between TR and adverse outcomes after cardiac surgery. 1 , 3 , 18 , 19 These studies were focused on narrow patient groups undergoing either mitral or aortic valve interventions. A seminal publication by Sagie 20 studied 318 patients undergoing percutaneous balloon mitral valvuloplasty for mitral stenosis and found TR to be among the most important predictors of procedural outcomes and 4-year mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported an association between TR and adverse outcomes after cardiac surgery. 1 , 3 , 18 , 19 These studies were focused on narrow patient groups undergoing either mitral or aortic valve interventions. A seminal publication by Sagie 20 studied 318 patients undergoing percutaneous balloon mitral valvuloplasty for mitral stenosis and found TR to be among the most important predictors of procedural outcomes and 4-year mortality.…”
Section: Discussionmentioning
confidence: 99%
“…During follow-up, functional TR continues to progress in 97.5% of the patients with newly developed functional TR after the index event. The functional TR progression rate was highest in patients with moderate to severe RV dysfunction, > moderate MR, pulmonary hypertension, and LV dysfunction [34].…”
Section: Ischemic Tricuspid Regurgitationmentioning
confidence: 92%
“…In another longitudinal analysis study, but after percutaneous coronary intervention (PCI), Koren et al followed the evolution of functional TR in 134 patients presented with ischemic MR after myocardial infarction for a median follow-up of 5 years [34]. They excluded all other etiologies of TR such as primary tricuspid valve pathology, pulmonary hypertension, or RV leads.…”
Section: Ischemic Tricuspid Regurgitationmentioning
confidence: 99%
“…In specific, there is a close relation of TR with other valvular pathologies, as studies show that TR coexists with severe mitral regurgitation in 30–50% of patients and with severe aortic stenosis in 25% of patients [ 26 ]. Additionally, ischemic mitral regurgitation is strongly associated with development and progression of TR, while TR severity is proportional to the extent of the regurgitation [ 27 ]. Furthermore, studies showed that coexistence of TR at the time of surgery for mitral or aortic regurgitation adversely affects short- and long-term outcomes [ 28 , 29 ].…”
Section: Pathophysiology Of Tricuspid Regurgitationmentioning
confidence: 99%